Betaine attenuates pathology by stimulating lipid oxidation in liver and regulating phospholipid metabolism in brain of methionine‐choline–deficient rats. Issue 8 (23rd May 2019) - Ahmad, Nur Abu; Raizman, Merav; Weizmann, Nathalie; Wasek, Brandi; Arning, Erland; Bottiglieri, Teodoro; Tirosh, Oren; Troen, Aron M.
ABSTRACT: Methyl‐donor deficiency is a risk factor for neurodegenerative diseases. Dietary deficiency of the methyldonors methionine and choline [methionine‐choline–deficient (MCD) diet] is a well‐established model of nonalcoholic steatohepatitis (NASH), yet brain metabolism has not been studied in this model. We hypothesized that supplemental betaine would protect both the liver and brain in this model and that any benefit to the brain would be due to improved liver metabolism because betaine is a methyl‐donor in liver methylation but is not metabolically active in the brain. We fed male Sprague‐Dawley rats a control diet, MCD diet, or betaine‐supplemented MCD (MCD+B) diet for 8 wk and collected blood and tissue. As expected, betaine prevented MCD diet‐induced NASH. However, contrary to our prediction, it did not appear to do so by stimulating methylation; the MCD+B diet worsened hyperhomocysteinemia and depressed liver methylation potential 8‐fold compared with the MCD diet. Instead, it significantly increased the expression of genes involved in β‐oxidation: fibroblast growth factor 21 and peroxisome proliferator–activated receptor α. In contrast to that of the liver, brain methylation potential was unaffected by diet. Nevertheless, several phospholipid (PL) subclasses involved in stabilizing brain membranes were decreased by the MCD diet, and these improved modestly with betaine. The protective effect of betaine is likely due to the stimulation of β‐oxidation in liver and the effects on PL metabolism in brain.—Abu Ahmad, N., Raizman, M., Weizmann, N., Wasek, B., Arning, E., Bottiglieri, T., Tirosh, O., Troen, A. M. Betaine attenuates pathology by stimulating lipid oxidation in liver and regulating phospholipid metabolism in brain of methionine‐choline–deficient rats. FASEB J. 33, 9334–9349 (2019). www.fasebj.org